Macrophage Polarization in Cerebral Aneurysm: Perspectives and Potential Targets - Lingmin Shao; Xingping Qin; Jia Liu; Zhihong Jian; Xiaoxing Xiong; Renzhong Liu (Journal of Immunology Research)
Cerebral aneurysms (CAs) have become a health burden not only because their rupture is life threatening, but for a series of devastating complications left in survivors. It is well accepted that sustained chronic inflammation plays a crucial role in the pathology of cerebral aneurysms. In particular, macrophages have been identified as critical effector cells orchestrating inflammation in CAs. In recent years, dysregulated M1/M2 polarization has been proposed to participate in the progression of CAs. Although the pathological mechanisms of M1/M2 imbalance in CAs remain largely unknown, recent advances have been made in the understanding of the molecular basis and other immune cells involving in this sophisticated network. We provide a concise overview of the mechanisms associated with macrophage plasticity and the emerging molecular targets.